2015
DOI: 10.4103/0976-9668.149101
|View full text |Cite
|
Sign up to set email alerts
|

A study of blood utilization in a tertiary care hospital in South India

Abstract: Background:Monitoring blood utilization helps in effective management of blood stock to meet present and future demands in a hospital. Hence, we analyzed the age, gender and frequency distribution of each blood product used in different diseases conditions.Materials and Methods:We included all blood products utilized from January 2008 to December 2012 in our tertiary care hospital in South India. The primary and secondary discharge diagnoses (International Classification of Diseases [ICD-10]) were matched with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…Joshi et al also found increased number of whole blood utilization compared to other components. In western countries, there is decline in the usage of whole blood [4]. Anshoo et al [15] and Venkatachalapathy and Subhashish [3] documented increased distribution of packed red cells among blood components which is correlating with our findings.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Joshi et al also found increased number of whole blood utilization compared to other components. In western countries, there is decline in the usage of whole blood [4]. Anshoo et al [15] and Venkatachalapathy and Subhashish [3] documented increased distribution of packed red cells among blood components which is correlating with our findings.…”
Section: Discussionsupporting
confidence: 81%
“…Anshoo et al [15] and Venkatachalapathy and Subhashish [3] documented increased distribution of packed red cells among blood components which is correlating with our findings. Ambroise et al [4] showed increased issue of FFP and Platelets in …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Blood has become scarce resource because of advances in blood bank techniques, increased frequency of complex surgical procedures, aging populations, initiatives aimed at improving health care standards and decrease in donor availability due to stringent screening criteria. [9] Studies have revealed high proportion of inappropriate use of blood transfusion often in both developed and developing countries. [8,10] This study aims to evaluate the prevalence of TTI in donors in blood bank of Institute of Social Obstetrics and Government Kasturba Gandhi Hospital for Women and Children, Triplicane, Chennai, India over a period of one year.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%
“…Patients may receive transfusions of a single blood component (e.g., only red blood cells [RBCs]), or they may be transfused with several different blood products (multicomponent transfusion). The existing literature on blood product utilization has largely focused on describing individual blood product usage, consequently ignoring patients who receive multicomponent transfusions . Multicomponent transfusion recipients differ from patients transfused with only one type of blood product, as they likely have higher illness acuity or a very different medical condition, which would necessitate the transfusion of several different blood components.…”
mentioning
confidence: 99%